Development of Low Cost High Rise Building using Austenitic-Ferritic Material in Nano-Scale Environmental Challenges to Sustain a Green - Salim, Mohd Azli; Noordin, Aminurrashid; Abdul Munir, Fudhail (Praise Worthy Prize, 2011)
Nanotechnology is become one of the method to produce and develop a green building. Many definition of green building was created today. In this paper, it was presented a green building that used a nanotechnology to produce an understanding microstructure of material. This material is used to develop a high potential structure that can be used in high rise building. By using this material, sustainability is the capability of a material or design to endure. In biological science, it was define as how the system remained diverse and productive versus time period. For human being, it was described as a potential of long term period of maintenance where it was environmental, economic and many more. This paper describes more on energy and cost in design high rise building to endure. The proposed design agrees that the distribution load and strength of structure is two times higher compared with the conventional structure. According to this result, the sustainability is achieved in word of economic design.